Responsabilidade civil e causas de quebra do nexo causal no Código de Defesa do Consumidor: peculiaridades do risco de desenvolvimento - Andrade, Vitor Morais de (2016)
This thesis examines the problem of civil responsibility and development risk in the Consumer Protection and Defence Code (Law no 8.078/90). For this reason, a critical approach on the subject of civil liability has been developed, which is analysed from juridical, economic and social viewpoints. The observation that no uniform position exists in either national doctrine or jurisprudence concerning the liability of the supplier in cases of development risk is seen as a regulatory gap, which ultimately undermines the defence of consumer interests. The work demonstrates, by putting forward concrete cases, the gains obtained when losses may previously have been limited, which allows for suppliers and society as a whole to manage this risk more effectively, either by taking out insurance or even by creating governmental or sector-based funds which are in a position to assume the risk of indemnifications, within the framework of established legislation. The examples which have been examined show that in Brazil cases of liability through development risk only succeeded in compensating those consumers who were affected, due to their participation in Social Security Systems, which implies that workers, as well as society as a whole, participated financially in constituting the capital used to compensate consumers in the case of consumer-related accidents. This demonstrates the extent to which it is necessary for the judicial system to adjust and create conditions for a differentiated treatment concerning consumer accident risk liability, aimed simultaneously at safeguarding the integral compensation of the affected consumer, while ensuring that the costs of this compensation are met by the supplier or potential insurance funds which it has helped to set up, as a matter of lawconsumo, mirando a garantire, allo stesso tempo, il risarcimento integrale per il consumatore danneggiato e che i costi, per tale risarcimento, siano attribuiti unicamente al fornitore o a eventuali fondi o assicurazioni costituiti con la sua partecipazione, giacché si tratta di una regola di giustizia